440-P: The Effects of DPP-4 Inhibitors on Plasma Catecholamines and Their Metabolites in Patients with Type 2 Diabetes - PARK, IE BYUNG; LEE, DAEHO; LEE, KIYOUNG (Diabetes (New York, N.Y.), 2019)
Previous preclinical and clinical studies have raised a concern that dipeptidyl peptidase 4 inhibitors (DPP-4i) increased sympathetic activity, which may be related with increased risk of heart failure in DPP-4i-treated type 2 diabetics. In this study, we aimed to evaluate the relationship between DPP-4 activity and catecholamine secretion in patients with type 2 diabetes. Patients with type 2 diabetes (n=119) and normal healthy control subjects (n=25) participated in this cross-sectional study which included the measurement of serum DPP-4 activity and plasma levels of epinephrine (Epi), norepinephrine (NE), metanephrine (MET) and normetanephrine (NMET), other blood and urine biochemical tests, and the collection of demographic and clinical data. The median ages of patients with type 2 diabetes and healthy control subjects were 61 and 56 years, respectively. Compared with the control group, patients with type 2 diabetes were associated with lower plasma levels of catecholamines and their metabolites. In DPP-4i-treated diabetic patients (n=86) had lower plasma NMET level compared with other antidiabetic treatment group (n=36) [0.31 (IQR: 0.21, 0.43)] nmol/L vs. 0.41 (0.29, 0.46) nmol/L, p<0.05], while the plasma concentrations of the two catecholamines and MET were comparable. The difference in plasma NMET level between the two treatment groups was not affected by beta-blocker and angiotensin II receptor blocker therapy, respectively. Additionally, in DPP-4i-treated type 2 diabetics, DPP-4 activity showed inverse correlations with plasma levels of NE (r=-0.312, p<0.01) and NMET (r=-0.275, p<0.05). However, those inverse correlations were not observed in the healthy control group and type 2 diabetics treated with non-DPP-4i antidiabetic agents. Our results suggest that DPP-4i treatment in type 2 diabetics affects NE release from sympathetic nerve in a DPP-4 inhibitory action-dependent manner.